Tendencies in juvenile justice systems in Peru – 2010-2022 - Van der Maat, Bruno (2023)
This investigation presents the evolution in the three juvenile justice systems that exist in Peru, from 2010 to 2022. The tendencies and characteristics of each system will be examined. As the interrelationsbetween the three systems will be analyzed, a general hypothesis will be presented in order to explain the causes of the described tendencies. It will be highlighted that the implementation of «alternative» juvenile justice systems has not resulted in a decrease of juveniles in the closed system, on the contrary, more juveniles have been drained into the three juvenile justice systems.